Structural insights into the activation of the human prostaglandin E 2 receptor EP1 subtype by prostaglandin E 2 - Xue Meng; Yang Li; Jiuyin Xu; Kai Wu; Wen Hu; Canrong Wu; H. Eric Xu; Youwei Xu (Proceedings of the National Academy of Sciences, 2025)
Prostaglandin E 2 (PGE 2 ) mediates diverse physiological processes through four G protein–coupled receptor subtypes (EP1–EP4). While structures of EP2, EP3, and EP4 have been determined, the structural basis for PGE 2 recognition and activation of the EP1 receptor subtype has remained elusive due to its inherent instability. Here, we present the cryoelectron microscopy structure of the human EP1 receptor in complex with PGE 2 and heterotrimeric Gq protein at 2.55 Å resolution, completing the structural characterization of the EP receptor family. Our structure reveals a unique binding mode of PGE 2 within EP1, involving key interactions with residues in the orthosteric pocket. Notably, we observe a less pronounced outward displacement of transmembrane helix 6 compared to other EP receptor subtypes, suggesting a distinct activation mechanism for EP1. Through extensive mutational analyses, we identify critical residues involved in PGE 2 recognition, EP1 activation, and Gq protein coupling. By overcoming the challenges associated with the instability of EP1, our findings provide valuable insights into the subtype-specific activation mechanisms of EP receptors and lay the foundation for the development of more selective EP1-targeted therapeutics.